Ukraine : Technical Assistance Report-Reforming the State Fiscal Services. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2016)
The SFS was established in 2014 as the successor to the Ministry of Revenue and Duties (MRD), and with three components-tax, customs and tax police. Following the turbulence arising from mid-year leadership changes in the SFS, reform momentum was invigorated and a number of important initiatives are being pursued. Since May 2015, a comprehensive reform plan has been approved; execution of the plan has commenced; many regional and local leaders were replaced; a change director was appointed; integrity programs were expanded; and a set of indicators that provide for a substantial lift in organization performance are being pursued. There are preparations for ambitious changes to organization structure which will merge the field networks across tax and customs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet